Persistence of KIRneg NK cells after haploidentical hematopoietic stem cell transplantation protects from human cytomegalovirus infection/reactivation - Di Vito, Clara; Coianiz, Nicolò; Calvi, Michela; Terzoli, Sara; Zaghi, Elisa; Puccio, Simone; Frigo, Alessandro; Mariotti, Jacopo; De Philippis, Chiara; Mannina, Daniele; Sarina, Barbara; Mineri, Rossana; et al. (Frontiers in Immunology, 2024)
Haploidentical hematopoietic stem cell transplantation (h-HSCT) is a therapeutic option to cure patients affected by hematologic malignancies. The kinetics and the quality of immune-reconstitution (IR) impact the clinical outcome of h-HSCT and limit the onset of life-threatening Human Cytomegalovirus (HCMV) infection/reactivation. Natural Killer (NK) cells are the first lymphocytes that recover after h-HSCT and they can provide rapid innate immune responses against opportunistic pathogens. By performing a longitudinal single-cell analysis of multiparametric flow-cytometry data, we show here that the persistence at high frequencies of CD158b1b2jneg/NKG2Apos/NKG2Cneg/NKp30pos/NKp46pos (KIRneg) NK cells is associated with HCMV infection/reactivation control. These KIRneg NK cells are “unlicensed”, and are not terminal-differentiated lymphocytes appearing early during IR and mainly belonging to CD56bright/CD16neg and CD56bright/CD16pos subsets. KIRneg NK cells are enriched in oxidative and glucose metabolism pathways, produce interferon-γ, and are endowed with potent antiviral activity against HCMV ex vivo. Decreased frequencies of KIRneg NK cells early during IR are associated with clinically relevant HCMV replication. Taken together, our findings indicate that the prolonged persistence of KIRneg NK cells after h-HSCT could serve as a biomarker to better predict HCMV infection/reactivation. This phenomenon also paves the way to optimize anti-viral immune responses by enriching post-transplant donor lymphocyte infusions with KIRneg NK cells.